High-pressure high-temperature synthesis of NdRe2 - Hussein, Zain; Kazemiasl, Nazanin; Hussaini, Kenan; Vaquero, Lia; Barkova, Olga; Drozd, Vadym; Chariton, Stella; Prakapenka, Vitali; Chuvashova, Irina (Frontiers in Chemistry, 2024)
In this study, we report the synthesis of a new cubic neodymium-rhenium metallic alloy NdRe2 through the utilization of high pressure and laser heating in a diamond anvil cell. NdRe2 crystallizes in the Fd3¯m space group with a lattice parameter equal to 7.486 (2) Å and Z = 8 at 24 (1) GPa and 2,200 (100) K. It was studied using high-pressure single-crystal X-ray diffraction. The compound crystallizes in the cubic MgCu2 structure type. Its successful synthesis further proves that high-pressure high-temperature conditions can be used to obtain alloys holding a Laves phase structure. Ab initio calculations were done to predict the mechanical properties of the material. We also discuss the usage of extreme conditions to synthesize and study materials present in the nuclear waste.